250 cases in clinical medicine - Baliga, R. R (New York : Elsevier/Saunders, 2003)
"Now in its fourth edition, this portable, versatile and practical self-assessment text is designed to help undergraduate and postgraduate candidates pass clinical examinations in general internal medicine across the English-speaking world."--Publisher's website
Cardiovascular system -- Neurology -- Respiratory system -- Abdomen -- Rheumatology -- Endocrinology -- Dermatology -- Fundus -- Miscellaneous
Includes bibliographical references and index
Keywords: Clinical medicine -- Case studies; Medicine -- Case studies; Clinical Medicine; Great Britain; Case Reports; Problems and Exercises; Case studies